When on Earth? history as you've never seen it before - Dorling Kindersley, Inc (New York, New York DK Publishing, 2015)
Incredible maps show where history was made. Much more than an atlas or a history book, When on Earth? charts global historical events through stunning world maps. A truly visual guide to discovering when, where, and why things happened, When on Earth? presents history as a series of stunning, specially commissioned historical maps of the world. Each of these maps charts a key global event, such as the migration of the earliest humans, the spread of the Black Death, or the European, African, and Pacific theaters of World War II
The ancient world -- The medieval world -- The modern world -- The 20th and 21st centuries
History
Includes index
13
Keywords: World history -- Juvenile literature